The impact of electronic development in public administration an analytical - Khalil اسراء عبد السلام (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The emergence of the information revolution has brought about many changes in people’s lives, and countries need to adapt to these changes. In this context, a new type of work based on adapting to advanced means of communication and their requirements, represented by electronic planning, electronic guidance, and electronic management and supervision, has emerged, which demonstrates the importance of electronic work. Advanced governments, realizing the importance of this electronic work, began to apply different information programs and started to use the concept of electronic management or the development of (e-government) in the state sector to determine the work of the public sector and utilities, providing the best services in the easiest means in a few aspects. The government is not obliged to apply this modern management concept and it is left to its discretion and to the extent of its capabilities and potential to apply this system. The development of electronic management in a simplified way is the transformation of government administration to perform its tasks with respect to services between citizens and each other, using the costs required for the development of electronic management and such electronic transformation process. The researcher conducted an analytical study consisting of two axes: the first axis "development of electronic management" and the second axis "public administration".